HUBUNGAN PENDEKATAN BEHAVIORISTIK TERHADAP KONSENTRASI BELAJAR SISWA SD 2 HADIPOLO KUDUS - Andi Saputro; Imaniar Purbasari; Fina Fakhriyah (Jurnal Muara Pendidikan, 2022)
The low understanding of students in learning can be caused by a lack of concentration in students' learning in the learning process. this is evidenced by the fact that he met at SD 2 Hadipolo. The purpose of this study was to determine the relationship between the behavioristik approach and the concentration of students' learning in the learning process. The method in this research is quantitative correlation with instrument validation using two variable indicators, namely the behavioristik approach including readiness, training, as well as the influence and concentration of learning including cognitive behavior, affective behavior, and psychomotor behavior. The results of this study indicate that the behavioristik approach has a strong relationship with the concentration of student learning in grade III SD 2 Hadipolo Kudus. The statement was obtained from the results of the Pearson Correlation hypothesis test on the SPSS version 26 application with a significance value of 0.000. The conclusion of this study is that the behavioristik approach has a strong relationship with the concentration of student learning in class III SD 2 Hadipolo Kudus with a significance value of 0.000 <0.05 which means that it is correlated with the findings in the learning process of students who initially did not dare to express what they felt to be dare to express something, students who initially lacked confidence in conveying the answers to the teacher's questions, became confident to convey the questions given by the teacher. In line with what Lawson said in (Mulyadi, 2016), the approach is a learning strategy used by students to increase effectiveness in the learning process.